Lightweight engineered cementitious composites with self cleaning properties - Chen, Yongjia (2018)
Engineered cementitious composites (ECC) is the design modifications done to the microstructure to have the ability to go through a strain-hardening phase with improved tensile ductility as compared to normal cement composites. The applications of ECC have been expanding, including lightweight building façade and road pavements, making the ability to self-clean an advantageous and economical property to possess in the material. In this study, the aim is to study three different types of TiO2 and determine the best performing type to impart the photocatalytic properties into the different ECC mixes for the self-cleaning purposes. The analysis of the different types of TiO2 will done by assessing the self-cleaning abilities and efficiency over a few cycles. Influence of addition of TiO2 content, effect of white cement and the addition of air entraining agent (AEA) to decrease the density of the concrete were also studied and the mechanical properties were evaluated by various methods. The result shows that the cleaning efficiency of TiO2 decreases over time as the surface gets more stained, which could be further investigated on to maintain the efficiency which will bring about economic benefits. An increase in TiO2 content increased the compressive strength properties and self-cleaning property but decreased the tensile strength. The addition of AEA into the compositions resulted in a decline in both the compressive and tensile strength, and does not meet the fundamental requirement for ECC tensile strain-hardening property and does not favour the steady-state crack propagation.